Bank Characteristics, Financial Crises and Nonperforming Loans: A Panel Analysis on Malaysia’s Commercial Banks - Normah Erra Zulkifli; Zuriyati Ahmad (UIN Mataram, 2021)
The previous crises witnessed the system of Malaysian banks has been facing a large number of nonperforming loans. The arising of nonperforming loans problem however becomes worse when the bank fails to manage its management properly and efficiently. Therefore, this study tries to investigate the impact of bank characteristics and financial crises on nonperforming loans in Malaysia’s commercial banks. Panel data analysis is employed with the data of six (6) commercial banks spanning from the period of 1998 to 2019. The result depicted that return on asset, loan to asset and non-interest income also significantly influence nonperforming loan. While total loan found to have insignificant relationships with the variation of nonperforming loans. The financial crisis revealed a positive and significant impact on the nonperforming loans. The result obtained suggests that banks and the government need to prepare for the high variation of nonperforming loans if there are weaknesses in bank characteristics and during the economic downturn.